Lighting intensity control system using ESP32 - Susandi, Agung Suheru; Basrah Pulungan, Ali (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Efficient lighting that can be controlled flexibly is an important requirement in supporting comfort and energy efficiency, especially in residential environments. This research designs a lighting control system that can be accessed through various methods, such as touch screens, mobile applications, and physical switches, to provide flexibility in setting light intensity according to user needs. This system design uses an ESP32 microcontroller as the main control center connected to relays, a TFT touchscreen-based interface, a physical switch, and an internet-based Blynk application. The light intensity setting is done using RBDdimmer-based AC dimmer module, and the power consumption monitoring is done through PZEM0-004T sensor. Control and monitoring data are synchronized in real-time between control methods. Test results show that the system is able to properly manage lighting through three control paths in a synchronous manner, even when an internet connection is not available. The system is capable of automatically saving and restoring the last status, and makes it easy for users to adjust the lighting according to their preferences. With these features, this system can be implemented in an efficient IoT-based smart lighting concept